Sperm miR‐142‐3p Reprogramming Mediates Paternal Pre‐Pregnancy Caffeine Exposure‐Induced Non‐Alcoholic Steatohepatitis in Male Offspring Rats - Cong Zhang; Yu Guo; Yi Liu; Kexin Liu; Wen Hu; Hui Wang (Advanced Science)
Abstract Numerous studies have suggested a strong association between paternal adverse environmental exposure and increased disease susceptibility in offspring. However, the impact of paternal pre‐pregnant caffeine exposure (PPCE) on offspring health remains unexplored. This study elucidates the sperm reprogramming mechanism and potential intervention targets for PPCE‐induced non‐alcoholic steatohepatitis (NASH) in offspring. Here, male rats are administrated caffeine (15–60 mg kg−1/d) by gavage for 8 weeks and then mated with females to produce offspring. This study finds that NASH with transgenerational inheritance occurred in PPCE adult offspring. Mechanistically, a reduction of miR‐142‐3p is implicated in the occurrence of NASH, characterized by hepatic lipid metabolism dysfunction and chronic inflammation through an increase in ACSL4. Conversely, overexpression of miR‐142‐3p mitigated these manifestations. The origin of reduced miR‐142‐3p levels is traced to hypermethylation in the miR‐142‐3p promoter region of parental sperm, induced by elevated corticosterone levels rather than by caffeine per se. Similar outcomes are confirmed in offspring conceived via in vitro fertilization using miR‐142‐3pKO sperm. Overall, this study provides the first evidence of transgenerational inheritance of NASH in PPCE offspring and identifies miR‐142‐3p as a potential therapeutic target for NASH induced by paternal environmental adversities.